Sistema intensivo (SRI) de dos variedades de arroz (oryza sativa) bajo dos prácticas de riego con diferente número de plántulas por sitio. - Sarco Camba, Leandro Gaudencio (2011)
The present investigation was carried out the lands of the Agricultural Technical School “Galo Plaza Lasso” enclosure the Souls, city of Daule, County of the Guayas, in the sector independence. The duration of the experimental work in field was of 160 days. They thought about the following objectives. They thought about the following objectives: a) Determine the shafts incidence in the cultivation of rice (Oryza sativa) variety INIAP 11 and INIAP14 with the system Sri, b) to Establish the best yield in the 9 treatments in study and c) to establish the best relationship benefit/cost in the treatments in study. The treatments under study were: T1 INIAP 11 + a plant for place + watering for flood, T2 INIAP 11 + a plant for place + watering intermittent, T3 INIAP 11 + three plants for place + watering for flood, T4 INIAP 11 + three plants for place + watering intermittent, T5 INIAP 14 + a plant for place + watering for flood, T6 INIAP 14 + a plant for place + watering intermittent, T7 INIAP 14 + three plants for place + watering flood,T8 INIAP 14 + three plants for place + watering intermittent and T9(witness) variety Carbajal + five plants for place + flood. You uses a factorial arrangement (2x2x2+1) prepared at random in the experimental design of complete blocks (DBCA) with 3 repetitions. To establish the differences among the stockings of the treatments the test of multiple ranges it was used from Tukey to 95% of probability and the variation coefficient is expressed in percentage. The variables 1 plant Height were analyzed, macollamiento, longitude of the spike, number of full grains for spike, number of cobs for m2, longitude of the pounded grain and yield for hectare, production costs, utility and relationship benefit/cost. When locating a single plant for place one has bigger shafts number for plant. In the treatment T3 with 7,37mm, one has the biggest grain longitude in this treatment three it plants of rice of the variety INIAP it was used 11 by place and the cultivation stayed with sheet of permanent water. The treatment T3 with 10.975,00 Kgha-1 presents the biggest production of rice for hectare, in this treatment it was used, three it plants for place of the variety INIAP 11 and he/she stayed the cultivation low sheet of permanent water.